A Hybrid Fuzzy AHP/VIKOR Approach to Funding Strategy Selection for Advanced Prosthetic and Orthotic Medical Devices in Low-Income Countries: A Case of Pakistan. (13th October 2022) - Ahmed, Irfan; Feng, Bo; Abdul, Daud; Feng, Junwen
Abstract : In the context of advanced prosthetic and orthotic medical devices, funding is a major challenge, especially in low-income countries. This research aims to investigate the best funding solution for such medical devices to offer disabled people a better quality of life and improve their health and economic situation. This is the first time such methods are being used in a study based on related research involving a fuzzy analytic hierarchy process (FAHP)/VIekriterijumsko KOmpromisno Rangiranje (VIKOR) model to find the best funding source. A survey questionnaire created by the author and completed by Pakistan subject experts was used to analyze data via a weightage value ranking system as an assessment tool. Prioritization of funding alternatives was based on main criteria and subcriteria. Limitations include sample number of study participants, amount of data collected, number of models used, and time constraints. Potential funding sources were ranked based on a VIKOR weightage value model using a hybrid decision-making process that showed results as "private insurance" having a weightage value of (0.1956) as being the best funding source since they are having the minimum weightage and then next from best to least they were "need-based" with a weightage value of (0.2510), "self-pay" with a weightage value of (0.7970), and finally "government-based" having a weightage value of (0.9636). Implications of this study conclude that the proposed model efficiently finds the best funding sources for advanced prosthetic and orthotic (P&O) medical devices in low-income countries. Executing this model in low-income countries such as Pakistan can help solve P&O medical device coverage challenges and offer disabled people better opportunities to work and contribute to their quality of life and economy.